THE CO-OPERATIVE STUDY OF KUROSHIO (CSK): IS IT BENEFICIAL FOR INDONESIA? - Mulyadi, Hanung Agus; Syahailatua, Augy; Arifin, Zainal (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2019)
The Cooperative Study of Kuroshio and its marginal seas (CSK) is one of the international joint research project conducted in the Western Pacific region. Many Asian countries had been involved in this project from 1965 to1979. Data and information from the CSK are enormous and cover wide-ranging aspects of marine science from the Kuroshio and adjacent regions (e.g. physical aspects, biological aspects and biogeochemical aspects). Indonesia had committed to participate actively in several marine research programs in the area linked to the CSK program by conducting marine research in its internal waters. This essay explained the CSK from biological aspects and Indonesia perspective. During the CSK, biological aspects (e.g. primary productivity, zooplankton biomass, and fisheries) were studied intensively. Indonesia conducted research in internal waters (Natuna Sea and the Java Sea) for oceanography monitoring and fish stock assessment. Participation in the CSK program allowed Indonesia to pursue the establishment of the National Center for Ocean Research (NCOR), develop human capacity building, research properties and standardized all techniques and procedures related to oceanography aspects. After the CSK, Indonesia has continued to conduct marine research linked to the previous study. We learn a lot from the past CSK that a key to succeeding in running this program depending on co-operative spirit, enthusiastic in understanding marine science from the region and enhancing human capacity for doing better marine research.